A semiconducting layered metal-organic framework magnet - Yang, Chongqing; Dong, Renhao; Wang, Mao; St Petkow, Petko; Zhang, Zhitao; Wang, Mingchao; Han, Peng; Ballabio, Marco; Braeuninger, Sascha A.; Liao, Zhongquan; Zhang, Jichao; Schwotzer, Friedrich; et al. (Nature Communications, 2019)
The realization of ferromagnetism in semiconductors is an attractive avenue for the development of spintronic applications. Here, we report a semiconducting layered metal-organic framework (MOF), namely K3Fe2[(2,3,9,10,16,17,23,24-octahydroxy phthalocyaninato)Fe] (K3Fe2[PcFe-O8]) with spontaneous magnetization. This layered MOF features in-plane full π-d conjugation and exhibits semiconducting behavior with a room temperature carrier mobility of 15 ± 2 cm2 V−1 s−1 as determined by time-resolved Terahertz spectroscopy. Magnetization experiments and 57Fe Mössbauer spectroscopy demonstrate the presence of long-range magnetic correlations in K3Fe2[PcFe-O8] arising from the magnetic coupling between iron centers via delocalized π electrons. The sample exhibits superparamagnetic features due to a distribution of crystal size and possesses magnetic hysteresis up to 350 K. Our work sets the stage for the development of spintronic materials exploiting magnetic MOF semiconductors.
CRIS-Team Scopus Importer:2022-04-14